Emotional exhaustion in Peruvian university students in the context of the COVID-19 pandemic - Estrada Araoz, Edwin Gustavo (2022)
The present research aimed to describe the emotional exhaustion of Peruvian university students from the professional career of Education in the context of the COVID-19 pandemic. The approach was quantitative, the design was non-experimental, and the type was descriptive, cross-sectional. The sample consisted of 232 students, to whom the Emotional Tiredness Scale was applied, an instrument with adequate levels of reliability and validity. According to the results, the majority of students presented high levels of emotional fatigue and it was determined that the prevalence of this variable was significantly associated with the sex and age group of the students (p <0.05). It was concluded that it is necessary for the Psychopedagogy area of ​​the university to carry out the timely detection of students who suffer from emotional fatigue so that they recover their psychological well-being and apply preventive programs to reduce the prevalence of this phenomenon.